IMPLEMENTASI PEMBELAJARAN TEMATIK SECARA DARING DI MASA PANDEMI COVID-19 KELAS III MADRASAH IBTIDAIYAH AL’IMAROH CIKARANG BEKASI - Ardi Amsyah; Wiena Safitri; Anjar Sulistiyani (Bajang Institute, 2022)
The current pandemic phenomenon, the use of media in distance learning with the help of the internet network really helps the learning process. Thematic learning is learning that integrates several competencies from several subjects into thematic and interrelated forms. The thematic learning process provides direct experience to students and provides comprehensive and inseparable learning. The main problem that occurs is that teachers experience difficulties in implementing online thematic learning because previously the learning process was carried out face-to-face in the classroom. The purpose of this study was to analyze the implementation of online thematic learning during the Covid-19 pandemic Class III Madrasah Ibtidaiyah Al'Imaroh Cikarang Bekasi. This study uses a qualitative approach. Data collection techniques in research through observation, interviews and documentation. Data analysis techniques in the form of data reduction, data presentation and verification. The results of the research on the implementation of online Thematic learning during the Covid-19 pandemic in Class IIIA Madrasah Ibtidaiyah Al'Imaroh Cikarang Bekasi in the implementation process, the readiness of teachers and students is good. The implementation of online learning is going well. Teachers and students are able to use cellphones or laptop media properly. Student learning activities are carried out from home. Online learning uses devices (Gadgets) or laptops that are connected to the internet. Learning activities take place through the WhatsApp and Google Meet applications. The availability of devices (Gadgets) and laptops that are connected to good internet access is an absolute/mandatory thing for teachers and students. The obstacle found in the implementation of online Thematic learning is weak internet network connectivity. Poor internet access causes the learning process to run hampered. The series of online Thematic learning implementations are as follows 1) The activity begins with an online meeting using Google Meet. 2) The core activity, namely conveying learning material briefly. 3) Closing activity, in Thematic learning is not meant to end the lesson, but as a follow-up activity in the form of giving assignments. 4) Evaluation, namely the teacher gives assignments or questions to students in the Student Book to work on and complete at home in written form.